2016
DOI: 10.3758/s13423-016-1088-4
|View full text |Cite
|
Sign up to set email alerts
|

Using music to study the evolution of cognitive mechanisms relevant to language

Abstract: This article argues that music can be used in crossspecies research to study the evolution of cognitive mechanisms relevant to spoken language. This is because music and language share certain cognitive processing mechanisms and because music offers specific advantages for cross-species research. Music has relatively simple building blocks (tones without semantic properties), yet these building blocks are combined into rich hierarchical structures that engage complex cognitive processing. I illustrate this poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Research with individuals classed as 'tune deaf' has shown that poor musical performance tends to be associated with deficits in processing speech sounds (Jones et al, 2009). Taken together, the research indicates that music and language share some cognitive processing mechanisms, although the specific underlying mechanisms have not yet been established (Patel, 2017).…”
Section: The Relationship Between the Processing Of Music And Languagementioning
confidence: 99%
“…Research with individuals classed as 'tune deaf' has shown that poor musical performance tends to be associated with deficits in processing speech sounds (Jones et al, 2009). Taken together, the research indicates that music and language share some cognitive processing mechanisms, although the specific underlying mechanisms have not yet been established (Patel, 2017).…”
Section: The Relationship Between the Processing Of Music And Languagementioning
confidence: 99%
“…Here I concur with Chomsky (2010), Berwick and Chomsky (2016) and Chomsky (2016) that it is the flexible and unrestricted capacity for hierarchical embedding that is central to our species' cognitive uniqueness; I differ from them in seeing it as something that was flexible enough to immediately play a role in both structured thought and linguistic communication, as well as in other domains (it is only at this stage that music in its modern sense, replete with hierarchical structure, was born; cf. Patel, 2016). Elsewhere, I have explored the neural changes that were necessary to achieve this final stage of dendrophilia (Fitch, 2014)-but in short, dendrophilia requires both extensive connections between temporal and parietal areas and the prefrontal regions surrounding Broca's area (the arcuate fasciculus) as well as a great expansion of Broca's areas (Friederici, 2016;Rilling et al, 2008;Schenker et al, 2010).…”
Section: Stage 4 Syntactic Homo Sapiensmentioning
confidence: 99%
“…As this relationship showed a trend ( p = 0.02), one should consider this finding with caution. The relationship between music and language has been investigated for decades as reflected, among others, in the elegant work of Patel [ 42 ] or Peretz [ 43 ]. Various studies have confirmed a relationship between music listening and language as they share similar capacities in terms of perception and processing as well as neuroanatomical markers in language aptitude and musicality [ 41 – 48 ].…”
Section: Discussionmentioning
confidence: 99%